The highly promotive sensing performance of a single cerium doped SnO2 nanobelt sensor to ethanol. (September 2016) - Qin, Zhaojun; Liu, Yingkai; Chen, Weiwu; Wu, Yuemei; Li, Shuanghui
Abstract: Pure SnO2 nanobelts and Ce-doped SnO2 nanobelts were successfully synthesized and their morphology, microstructure, and elemental composition have been characterized by a series of techniques. The results reveal that Ce ions have incorporated into the lattice of SnO2 . The corresponding devices based on single nanobelt are fabricated and their sensitive properties are investigated systemically. The Ce-SnO2 sensor possesses a great response (8.2) to 100 ppm of ethanol at optimum temperature (230 °C). At the same time, its calculated theoretical detection limit is 78 ppb. The response and recovery time is quite short and air humidity has little effect on the performance of the sensor. In addition, the gas sensing mechanism of Ce-doped SnO2 is discussed.